(untitled) (The Lumbini Journal of Business and Economics, 2025)
Purpose: The study aims to analyze how Nepal’s fiscal decentralization has affected the economic growth and implementation status of elected government agencies of Sudurpashchim Province after introducing a new federal government structure. Methods: The study employed a descriptive and analytical research design that considered a quantitative approach using primary and time series data. Among 88 local-level governments, 46 were selected as samples. The primary data were collected through a semi-structured questionnaire and secondary data were collected from the annual report of the Ministry of Financial Affairs of Sudurpaschim Province. Results: The results show that around 50 percent of local-level governments only utilized the exclusive right and regarding the concurrent rights majority of the local-level governments are ambiguous. The expenditure of local level governments has been found significant and positive impact on economic growth. Whereas, the expenditure of provincial and federal governments has been found insignificant. Conclusion: The provincial government has a very small part of revenue-generating rights, for strengthening the federal system, more economic rights should be provided. The findings of the study are useful to policymakers and employees of local-level governments, provincial governments, and federal governments.